Behavior Meets Compliance: Applying the Theory of Planned Behavior to Taxpayer Conduct - Atik Djajanti; Regita Aprila Kristanti; Markonah Markonah (Journal of Business, Finance, and Banking, 2026)
Taxes are the main source of state revenue used to support national development. However, the level of taxpayer compliance in Indonesia has not yet reached the expected target. This study aims to analyze the influence of attitudes, subjective norms, and perceived behavioral control on taxpayer compliance in the Jabodetabek using the Theory of Planned Behavior. This study uses a survey method and with a convenience sampling technique, involving 100 respondents from individual taxpayers who are business owners. Data analysis was carried out using the multiple regression analysis method with the assistance of SmartPLS software. The results of this study show that the attitude, subjective norms, and perceived behavioral control have a positive and significant influence on taxpayer compliance.